Nursing Care Management: Influence on Bundled Payments. (January 2017) - Lentz, Shaynie; Luther, Brenda
Abstract : Fragmented and uncoordinated care is the third highest driver of U.S. healthcare costs. Although less than 10% of patients experience uncoordinated care, these patients represent 36% of total healthcare costs; care management interaction makes a significant impact on the utilization of healthcare dollars. A literature search was conducted to construct a model of care coordination for elective surgical procedures by collecting best practices for acute, transitions, and post-acute care periods. A case study was used to demonstrate the model developed. Care management defines care coordination as a model of care to address improving patient and caregiver engagement, communication across settings of care, and ultimately improved patient outcomes of care. Nurse-led care coordination in the presurgical, inpatient, and post-acute care settings requires systems change and administrative support to effectively meet the goals of the Affordable Care Act of reducing redundancy and costs while improving the patient experience. Nursing is the lynchpin of care management processes in all settings of care; thus, this model of care coordination for elective surgical admissions can provide nursing care management leaders a comprehensive view of coordinating care for these patient across settings of care during the predetermined time period of care. As bundled payment structures increasingly affect hospital systems, nursing leaders need to be ready to create or improve their care management processes; care coordination is one such process requiring immediate attention.